2022
DOI: 10.1002/slct.202201211
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Selective Aerobic Oxidation of 5‐hydroxymethylfurfural to 2,5‐diformylfuran at Moderate Reaction Conditions with Design of Experiments Approach

Abstract: Heterogeneous catalytic oxidation of 5-hydroxymethylfurfural (HMF) with molecular oxygen to 2,5-diformylfuran (DFF) was performed on aluminium oxide-supported ruthenium catalysts (Ru/Al 2 O 3 ). The ruthenium catalysts were analyzed by pH and Brunauer-Emett-Teller (BET) measurement, and potential side products measured by HPLC-UV. High catalyst activity with near-quantitative DFF yield (> 99.9 %) was achieved in toluene under moderate reaction conditions (90 °C, 0.2 MPa O 2 ). Various Al 2 O 3 supports were sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…DFF was prepared by oxidation of HMF in toluene with the heterogeneous catalyst 5 %Ru/Al 2 O 3 , which has been shown at 3 % Ru‐loading to have good catalytic activity and selectivity for this particular oxidation process [21] . Overall Yield of white DFF crystals after sublimation procedure was 73.26 %.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DFF was prepared by oxidation of HMF in toluene with the heterogeneous catalyst 5 %Ru/Al 2 O 3 , which has been shown at 3 % Ru‐loading to have good catalytic activity and selectivity for this particular oxidation process [21] . Overall Yield of white DFF crystals after sublimation procedure was 73.26 %.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the toxicity of HMF, which can also be found in foods such as honey, there are some studies that suggest HMF has beneficial as well as adverse human health outcomes, although acute toxicity only occurs with ingestion at high doses [20] . In contrast, DFF, a promising compound that can be produced by selective oxidation of HMF, is nontoxic and stable at room temperature [21] . DFF has already been used for various polyimines and urea resins, and we have successfully reported DFF as a formaldehyde substitute in the synthesis of aerogels with phenolic compounds [22]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruthenium on hydrotalcite at 120 °C in DMF achieved 92 % DFF yields (Table 1, Entry 6), [23] and ruthenium on activated carbon at 2 MPa O 2 in toluene at 120 °C yielded 96 % DFF (Table 1, Entry 7) [24] . We previously reported the high DFF selectivity of >99.9 % for 3 % Ru on γ‐Al 2 O 3 in toluene at relatively mild reaction conditions of 90 °C and 0.2 MPa O 2 (Table 1, Entry 8) [25] …”
Section: Introductionmentioning
confidence: 92%
“…Integrated biorefineries have been receiving more attention to increase the demand response in biogreen-circular economy for solving the environmental global issues leading to the sustainable development goals. The technological foresight of 2,5-furandicarboxylic acid (FDCA), which is the superior performance properties of the bio-based chemical building block for polyethylene furanoate are focused on the market attractiveness to replace polyethylene terephthalate. Particularly, 5-hydroxymethylfurfural (HMF) derived from cellulosic C6 sugars plays an important role in the chemical manufacture for the long-term investment to produce FDCA. A feasibility study of stepwise reaction mechanism for HMF oxidation shown in Scheme is proposed through two pathways, which include 5-hydroxylmethyl-2-furan carboxylic acid (HMFCA), 2,5-diformylfuran (DFF), and 5-formyl-2-furancarboxylic acid (FFCA) as intermediates. In the past decade, various catalysts were investigated for the significant reactivity in the oxidation of HMF to yield FDCA at the high temperature and pressure. , The historical FDCA production was conducted in the oxidation process of HMF by electrochemical oxidation, , biocatalysts, , heterogeneous catalysts, homogeneous catalysts, , and photocatalysts as well as the process without any catalyst. The utilization of homo- and heterogeneous catalysts is still promising for practical applications.…”
Section: Introductionmentioning
confidence: 99%